2003
DOI: 10.1007/s00429-003-0332-7
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and embryological characteristics of bronchial arteries in the rat

Abstract: There have been no previous reports of detailed macroscopic findings of the bronchial arteries, the nutrial vessels of the lungs. Also, previously, very little was known about the developmental processes of the bronchial arteries in rats and other laboratory animals. In the present study, we dissected bronchial arteries of adult rats from their origin to the pulmonary hilus, and examined developmental processes of bronchial arteries in a series of rat embryos. We observed one right bronchial artery and one lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…To perfuse the bronchial circulation synchronously with the pulmonary circulation, we modified the standard EVLP system to obtain a novel, dual‐perfusion EVLP system (dual EVLP) (Figure ). A preliminary anatomical analysis revealed that the bronchial arteries in rats arise from the right and left subclavian arteries (Figure S1). Therefore, after removal of the heart‐lung block, the distal portions of both subclavian arteries, and other large branches from aortic arch, including the carotid arteries, were ligated, and then bronchial artery perfusion was performed on EVLP in a retrograde fashion through an additional cannula inserted into descending aorta (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…To perfuse the bronchial circulation synchronously with the pulmonary circulation, we modified the standard EVLP system to obtain a novel, dual‐perfusion EVLP system (dual EVLP) (Figure ). A preliminary anatomical analysis revealed that the bronchial arteries in rats arise from the right and left subclavian arteries (Figure S1). Therefore, after removal of the heart‐lung block, the distal portions of both subclavian arteries, and other large branches from aortic arch, including the carotid arteries, were ligated, and then bronchial artery perfusion was performed on EVLP in a retrograde fashion through an additional cannula inserted into descending aorta (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…The bronchial arterial supply is known to be important in the overall lung reaction to injury, and thus anatomy and distribution are important in any animal model. There is considerable person-to-person variation in the human bronchial artery supply (99,135). These arteries invest the bronchi and extend throughout the length of the bronchial tree, with communication between the bronchial and pulmonary circulations in the terminal respiratory unit.…”
Section: Comparative Anatomymentioning
confidence: 99%
“…In mice (116), a bronchial artery supply exists, and there are interconnections between the two vascular systems at the level of the capillaries. Rats have a relatively similar system to humans, but with slightly different vascular derivations (135).…”
Section: Comparative Anatomymentioning
confidence: 99%